SMALL-SIGNAL MODELING OF PHEMTS AND ANALYSIS OF THEIR MICROWAVE PERFORMANCE - HEMAIZIA, Z.; SENGOUGA, N.; MISSOUS, M. (Courrier du Savoir, 2014)
Accurate extraction of the small-signal equivalent circuit elements of pseudomorphic high electron mobility transistors (pHEMT) is crucial for the design of microwave analog circuits such as low noise amplifiers (LNAs). This paper presents a direct analytical extraction procedure. Its efficiency is demonstrated on two different 1μm gate-length novel high breakdown InGaAs/InAlAs pHEMTs: one is grown on a GaAs while the other is on an InP substrate.